انتظار نعيم عبد تواجد الفطريات الخيطيه و الخمائر في مياه شبكات التوزيع للمياه للمناطق السكنيه وبعض المستشفيات في منطقة الناصرية - انتظار نعيم (University of Thi-Qar Journal of Science, 2019)
The main aim of this study was to analyse the occurrence of filamentous fungi and  yeasts in the drinking water of distribution systems ( tap water) as well as finding their correlation with some pollution indicator microorganisms .the presence of fungi was investigated in 140 sample of tap water (90 sample from districts ,50 sample from hospitals) in Nassiriyah city . in addition investigated of some standard pollution  indicator microorganisms . the filamentous fungi was isolated from 29 (23.22%) sample and yeasts From 25(27.77%) sample of 90 tap water sample of districts ,while the filamentous fungi was isolated from 16 (32%) and yeasts from 6 (12%) of 50 tap water  sample of hospitals. Prevailing genera were Aspergillus spp.the percentage of frequency of this genus was 26.42%,followed by Cladosporium spp. . (14.99%) and Penicillium spp.(10%) ,yeasts ,the prevailing genus was Candida spp. (18.57%) . There was a significant  correlation between counts of filamentous fungi and counts of Heterotrophic Plate  Count (HPC) in samples of districts water ,while the counts of yeasts were significantly correlated with counts of fecal coliform bacteria in samples of hospitals .thus ,taps water of distribution system for districts and hospitals could be considered transmission route for fungi that reduce drinking water quality and could constitute a potential infection diseases  for human mainly immunocompromised individuals .